100 classic hikes Oregon : Oregon Coast, Coast Range, Western Valleys, Columbia River Gorge, Cascade Range, Central Oregon, Wallowa Mountains, Southeast Oregon - Boschetto, Eli (Mountaineers Books, 2025)
"The varied landscapes of Oregon are a year-round hikers paradise, offering an abundance of volcanic peaks, dramatic coastlines, lush forests, wide-open high deserts, winding canyons, and sparkling alpine lakes. Hiking expert and author Eli Boschetto brings his deep knowledge and passion for trails and Oregon's hiking community to 100 Classic Hikes: Oregon. Designed for use by day hikers and backpackers alike, this new guidebook highlights the state's best natural spaces along with routes of historical or cultural significance. Boschetto provides options for both shortening or extending many hikes so everyone can find the route that matches their skill and energy level-and, of course, includes distance and time for each route as well as difficulty rating, elevation gain, permit information, and more"-- Provided by publisher.